Mulheres na Commedia dell’Arte - atuando entre máscaras e fogueiras: entrevista com Tania Passarini e Luca Comastri (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
Tania Passarini and Luca Comastri, Italian actors from Fraternal Compagnia APS gave an interview to Professor Dr. Maria Brígida de Miranda on May 8, 2024. They discussed historical documents that indicate the work of women in the Commedia dell'Arte companies from the sixteenth century onwards and reflected on the developments of the Second Wave of the feminist movement in Italy in relation to theatrical practice and the efforts of actress Eleonora Fuser to create the mask La Strega (The Witch). Tania and Luca revealed about the dramaturgy of their new production inspired by the sixteenth-century witch hunt manual - Malleus Maleficarum - The Hammer of the Witches.
Keywords: acting; Commedia dell’Arte; feminism; witch; woman